DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION TEACHING MATERIALS AQIDAH AKHLAK ELEMENT BASED ON RELIGIOUS MODERATION AT SMA NEGERI 1 PANYABUNGAN SELATAN - Dakran; Anhar; Zainal Efendi Hasibuan (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to develop Islamic Religious Education (IRE) teaching materials in the element of Aqidah and Akhlak based on religious moderation for eleventh-grade high school students. The background of this research lies in the limited availability of teaching materials that systematically integrate religious moderation values, whereas such values are crucial in shaping students’ character to become faithful, virtuous, and tolerant individuals in a pluralistic society. The research method employed is Research and Development (R&D), adopting the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of the trial involved material experts, media experts, Islamic Education teachers, and grade XI students. The research instruments included validation questionnaires, practicality questionnaires, and learning achievement tests. The collected data were analyzed using both quantitative descriptive and qualitative methods. The results indicate that the developed IRE teaching materials based on religious moderation are highly valid, with an average validity percentage of 89.58%. In terms of practicality, both teachers and students responded positively, categorizing the product as very practical and easy to use in the learning process. Regarding effectiveness, the use of these teaching materials successfully improved students’ learning outcomes, shown by the N-Gain score categorized as moderate, with 100% learning mastery achieved during the field trial. Therefore, this development contributes significantly to providing relevant, innovative, and contextual teaching media. The teaching materials not only facilitate cognitive competency achievement but also instill the values of religious moderation oriented toward strengthening faith, cultivating morality, and fostering tolerance, justice, and balance. This study is expected to serve as an alternative solution for curriculum development in Islamic Religious Education at the secondary level and as a reference for teachers in creating more meaningful learning